Pengaruh Variasi Bahan Pengendap pada Proses Purifikasi Enzim Bromelin dari Bonggol Nanas (Ananas Comosus L.) - Triastuti, Warlinda Eka; Tyas, Sunia Rahma Cahyaning; Zahrah, Hanifah Fauziyah; Bennani, Kabira; Cahyani, Erika Desi; Ramadita, Tatya Annur; Rahayu, Adel Frisca (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Waste from processed pineapples (pineapple core) is currently underutilized, despite the high content of the bromelain enzyme found in the fruit. This research aims to determine the effect of precipitating agents on the purification process of bromelain enzyme production using a phosphate buffer on the resulting enzyme yield and to analyze the effect of the precipitating agents on the purification process of bromelain enzyme production using a phosphate buffer on the bromelain enzyme activity. The variables used in this study were a 0.1 M phosphate buffer, 55%; 60%; 65%; 70%; 75% aseton concentration, 5%; 10%; 15%; 20%; 25% NaCl concentration, and 60%; 65%; 70%; 75%; 80% ethanol concentration. This study will be conducted in three stages, namely Extraction, Purification, and Drying. The highest yield was obtained with 60% aseton concentration (1.44%), 65% ethanol concentration (1.42%), and 15% NaCl concentration (2.2%). The optimal enzyme activity was obtained with 60% aseton concentration (20225.616 U/gr), 65% ethanol concentration (6266.765 U/gr), and 15% NaCl concentration (2281.357 U/gr). In conclusion, the best result for producing bromelain enzyme powder from pineapple cores is by using a 60% aseton concentration solvent.